2022
DOI: 10.3390/su142214822
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Eucalyptus Leaf Extract Application Extends the Sustainable Supply of Strawberries by Retaining Physicochemical Quality during Cold Storage

Abstract: Strawberry is a delicate fruit with a short shelf life after harvest. High metabolic activities and fungal decay deteriorate its quality. In an attempt to extend its shelf life and maintain its quality while retaining its antioxidant potential, the harvested fruits of strawberry cv. Chandler were dipped in 30% eucalyptus leaf extract (ELE). Weight loss, fungal decay index, percentage of decayed fruits, respiration rate, and electrolyte leakage were all reduced in ELE-treated strawberries. The enzymatic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
4
4
0
Order By: Relevance
“…5B). Similar ndings were reported by Haider et al [59] who reported 1.7 times higher CAT activity in ELE treated strawberries 15 days after storage compared to control fruits. Our study also con rms the ndings of Zhao et al…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…5B). Similar ndings were reported by Haider et al [59] who reported 1.7 times higher CAT activity in ELE treated strawberries 15 days after storage compared to control fruits. Our study also con rms the ndings of Zhao et al…”
Section: Resultssupporting
confidence: 90%
“…5B). Previously, similar ndings were obtained as increased SSC in apples [34,37,53], strawberries [28, 30,38,41,59], tomatoes [23,48], and litchi [47] in response to applied plant-based extracts during storage. In this study, the titratable acidity (TA) decreased with progression of storage period but the decrease was slightly lower in HWT + ELE treated chilies (0.46%) compared to the control (0.35%) after 20 days of storage (Fig.…”
Section: Juice Ph Ssc (%) Ta (%) and Ripening Indexsupporting
confidence: 69%
See 1 more Smart Citation
“…Biopesticides have long been attracting global attraction due to their safer strategy than conventional pesticides. Considering the importance of sustainable agriculture [ 173 , 174 , 175 , 176 ], Bacillus spp.-based bioproducts could be a promising addition to sustainable agriculture as there is a limited product range available. There is a dire need to explore the potential of Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…In cold storage, the CAT activity was increased as the days of storage increased. Increase in the catalase activity of strawberry fruits up to 5 days during storage period was observed by Haider et al (2022). The study checked the effect of application of Eucalyptus leaves extract on postharvest strawberry fruits.…”
Section: Catalase (Cat) Activitymentioning
confidence: 99%